A Memory-Saving Algorithm for Spectral Method of Three-Dimensional Homogeneous Isotropic Turbulence (Communications in Computational Physics, 2020)
Homogeneous isotropic turbulence has been playing a key role in the researchof turbulence theory. And the pseudo-spectral method is the most popularnumerical method to simulate this type of flow fields in a periodic box, where fastFourier transform (FFT) is mostly effective. However, the bottle-neck in this methodis the memory of computer, which motivates us to construct a memory-saving algorithmfor spectral method in present paper. Inevitably, more times of FFT are neededas compensation. In the most memory-saving situation, only 6 three-dimension arraysare employed in the code. The cost of computation is increased by a factor of 4, andthat 38 FFTs are needed per time step instead of the previous 9 FFTs. A simulation ofisotropic turbulence on 20483 grid can be implemented on a 256G distributed memoryclusters through this method.